Implementation of energy management in designing stage of building construction - Tahir, Mohamad Zamhari; Mohd Nawi, Mohd Nasrun; Baharum, Faizal (AENSI Journals, 2015)
The design stage in construction project, in fact, is one of the significant stages in a project life cycle.This research aims to emphasize the needs of energy saving element in the design stage of building to face the future changes of building’s energy consumption.This research still in its initial phase, therefore the findings and discussion is based on previous studies and looks into the key issues while exploring the potential for further research This research has been carried out to discover the importance of considering the energy management elements during the design stage of commercial building construction for the conventional building in Malaysia.The main reason is that in tropical climate, commercial buildings have very high energy needs usually during the peak periods of business hour.Hence, the research objective is to minimize the total energy consumption during the building occupancy besides various energy saving strategies that is usually implemented later in operation and maintenance stage.Overall this paper reviews the previous works and potential implementation to the industry in order to enhance this research for further investigation.